2006
DOI: 10.1103/physrevlett.96.077005
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of Vortex Shells and Magic Numbers in Mesoscopic Superconducting Disks

Abstract: We have studied vortex configurations in mesoscopic superconducting disks using the Bitter decoration technique. For a broad range of vorticities L the circular geometry is found to lead to the formation of concentric shells of vortices. From images obtained on disks of different sizes in a range of magnetic fields we traced the evolution of vortex states and identified stable and metastable configurations of interacting vortices. Furthermore, the analysis of shell filling with increasing L allowed us to ident… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
132
3
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(161 citation statements)
references
References 27 publications
25
132
3
1
Order By: Relevance
“…5, we observed a one dimensional vortex distribution on an annulus, and found that the vortex spacing (a) did not follow the Abrikosov lattice derived from the GL equation, 2 √3 ⁄ / for a close-packed hexagonal array; this equation leads to sparse vortices at low fields (H < 0.7 T) and dense vortices at high fields (H > 0.7 T). In previous measurements of mesoscopic superconducting disks [4,16,45], the first vortex is typically observed in the center of the disk in contrast to the results in Fig. 5.…”
Section: Islandscontrasting
confidence: 53%
See 1 more Smart Citation
“…5, we observed a one dimensional vortex distribution on an annulus, and found that the vortex spacing (a) did not follow the Abrikosov lattice derived from the GL equation, 2 √3 ⁄ / for a close-packed hexagonal array; this equation leads to sparse vortices at low fields (H < 0.7 T) and dense vortices at high fields (H > 0.7 T). In previous measurements of mesoscopic superconducting disks [4,16,45], the first vortex is typically observed in the center of the disk in contrast to the results in Fig. 5.…”
Section: Islandscontrasting
confidence: 53%
“…When the size of a superconductor becomes comparable with these characteristic lengths, the properties of the superconductor can change dramatically, including the critical temperature, critical magnetic field, and vortex structures. Early work focused on the effect of condensate confinement in mesoscopic disks [2][3][4], and the effect of symmetry [5] in comparing disks, squares [6], and mesoscopic triangles [7]. Focus on vortex states in mesoscopic superconductors, both theoretical and experimental, revealed multi-vortex Abrikosov-like states with spatial arrangements of singly quantized vortices, or giant vortex states depending on details of the condensate confinement [8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Skyrmions have many features in common with Abrikosov vortices in superconductors (28,29). They are both condensed into a triangular lattice in bulk or 2D films due to the minimization of their repulsive interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Very recently, Grigorieva et al 22 succeeded in the direct observation of vortex shells in mesoscopic superconducting Nb disks using the Bitter decoration technique. At fixed temperature, they studied well-defined shell structures containing up to 40 vortices and identified rules of shell filling and magic numbers, in agreement with Ref.…”
Section: Introductionmentioning
confidence: 99%